공항 특수경비조직의 내부서비스품질과 내부고객만족 및 경영성과의 관계 - 김찬선(Chan-Sun Kim); 이지은(Ji-Eun Lee); 조병해(Byung-Hae Jo) (한국콘텐츠학회 논문지, 12(4), 2012)
The purpose of this study is to investigate the relationship between internal service quality, internal customer satisfaction and management outcome of airport security agents. This study had selected special securities from Incheon airport of October, 2011 for population. Using judgment sampling method, 282 samples were drawn and were used for the final analysis. Questionnaire used in study is composed of total 43 questions and using SPSSWIN 18.0, frequency analysis, factor analysis, reliability analysis, multiple regression analysis and path analysis were performed. Cronbach's ${α}$ value which shows the reliability of the survey came out to be over .686. The conclusion is following: First, internal service quality of airport security agents affects internal customer satisfaction. That is, as corporality, responsiveness and empathy increase, internal supply satisfaction and job satisfaction also increase. Second, internal service quality of airport security agent affects job performance. That is, as corporality, reliability and responsiveness increase, non-financial performance and financial performance also increase. However, when empathy is not activated well, financial performance is decreased. Third, airport security agent…s internal customer satisfaction affects job performance. That is, as activation of internal supply satisfaction increases, nonfinancial performance and financial performance are increased. Fourth, airport special security agent…s inside quality of service exerts direction indirect effect in inside customers satisfaction and management result. That is, inside customers satisfaction is an important variable that mediate inside quality of service and management result. 이 연구의 목적은 공항 특수경비조직의 내부서비스품질과 내부고객만족 및 경영성과의 관계를 규명하는 데 있다. 이 연구는 2011년 10월 인천소재 공항에서 재직하고 있는 특수경비원들을 모집단으로 설정한 후 유의표집법을 이용하여 최종분석에 이용된 사례 수는 총 282명이다. 연구에 사용된 설문지는 총 43문항으로 구성되었으며, SPSSWIN 18.0을 이용하여 빈도분석, 요인분석, 신뢰도분석, 다중 회귀분석, 경로분석 등을 실시하였다. 설문지의 신뢰도는 Cronbach's ${α}$값이 .686이상으로 나타났다. 결론은 다음과 같다. 첫째, 공항 특수경비조직의 내부서비스품질은 내부고객만족에 영향을 미친다. 즉, 유형성, 대응성, 공감성 활동이 잘 이루어질수록 내부지원만족, 유형성, 대응성 활동이 잘 이루어질수록 직무만족은 증가한다. 둘째, 공항 특수경비조직의 내부서비스품질은 경영성과에 영향을 미친다. 즉, 유형성, 신뢰성, 대응성 활동이 잘 이루어질수록 비재무적성과, 유형성, 신뢰성 활동이 잘 이루어질수록 재무적성과는 증가한다. 반면, 공감성 활동이 잘 이루어지지 않을 경우 재무적성과는 감소한다. 셋째, 공항 특수경비조직의 내부고객만족은 경영성과에 영향을 미친다. 즉, 내부지원만족 활동이 잘 이루어질수록 비재무적성과 및 재무적성과는 증가한다. 넷째, 공항 특수경비조직의 내부서비스품질은 내부고객만족 및 경영성과에 직 간접적인 영향을 미친다. 즉, 내부고객만족은 내부서비스품질과 경영성과를 매개하는 중요한 변수이다.